THE ROLE OF MUSYRIFAH IN DEVELOPING SOCIAL ATTITUDES OF FEMALE STUDENT AT MA’HAD ISLAMIC UNIVERSITY MAULANA MALIK IBRAHIM MALANG 2021-2022 - Ummah, Mufidatul; Hidayat, Imam Wahyu (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Social attitude is an attitude that cannot immediately appear and attach to a person, but requires learning and habituation. We can find such a strong social attitude in the boarding school environment. Meanwhile, the problem that is currently being faced is that social attitudes are starting to fade and its impact is very much felt on the female students at the center of Ma'had Al- jami'ah Islamic University Maulana Malik Ibrahim Malang in 2021-2022. So students need a mentor role who can assist them in forming social attitudes. This is where the role of musyrifah is very necessary in addition to having to develop the knowledge of students, they also have the obligation to form the social attitudes of students. The purpose of this study is to find out that there is a role for Musyrifah in forming the social attitudes of female students of Ma'had UIN Malang by using descriptive qualitative research through observation, interviews and documentation to the caregivers, murobbiah, musyrifah and mahasantri. The data analysis used by the researcher is data reduction, data presentation and conclusion drawing or verification. The results showed that the social attitude to be developed by Ma'had UIN Malang is a social attitude that still pays attention to the concept developed by the campus, namely forming students with ulul albab characters, through the role of Musyrifah as educators and mentors, as role models and as motivators. However, in this formation, there are obstacles faced by the musyrifah, which come from internal factors in the form of the ego and self of the students, and from external factors such as friends and the environment of the students.